Model Sistem Dinamik untuk Evaluasi Skenario Pengelolaan Sampah di Kota Depok - Ika Artika; Mochammad Chaerul (Jurnal Wilayah dan Lingkungan, 2020)
One of the government programs to achieve the target of the National Waste Management Policy and Strategy is to build a regional landfill. To support regional landfill operations, the local governments which have utilized regional landfill need to prepare policies and strategies for optimizing waste management services in their area. Depok City is one of four cities that will served by Nambo Regional Landfill. The purpose of this study was to analyze various alternative policy scenarios to optimize waste management services in Depok City and determine their effects on the amount of waste transported to Nambo Regional Landfill. The policy analysis method used simulation model with a dynamic system approach. The simulation was conducted from 2020 to 2045. There were four scenarios, namely business as usual scenario, scenario A for the optimization of existing waste treatment facilities, scenario B which was based on local waste management policies and strategies, and scenario C for achieving 30% target of waste reduction. The simulation results showed the waste generation in 2045 was estimated to reach 3,426 tons/day. Results from all scenarios showed that the amount of waste disposed to landfill exceeds the maximum waste input to Nambo Regional Landfill. From scenario C, the amount of waste to be processed in the local landfill in 2045 was at least 1,180 tons/day. Depok City has a huge amount of waste and will continue to increase, so it is necessary to add waste treatment facilities and local landfill for the next 26 years. Landfill needs can be reduced by increasing waste treatment, but it requires greater waste management costs.